Feasibility Implementation E-Learning Based on CMS Wordpress for Professional Ethics - Supriyadi, M S; Yanto, H (KnE Social Sciences, 2018)
The success of the learning process at school can be seen from the learning result of learners. The result of learners at X Financial class of SMK Negeri 1 Kudus on Professional Ethics subject showed that there are still many students have not yet reached KKM (Minimum Required Score). This result indicated that the subject of Proffesional Ethich needed an innovation in the use of learning media so that the students able to understand easily and active during learning activity. The use of E-Learning based CMS Wordpress is expected to be effective in improving student learning outcomes. The aim of this research was to determine the influence of ELearning based CMS Wordpress on learning outcomes of learners and more effectively improve learning outcomes better than using conventional learning models. This research has designed quasi experimental nonequivalent control group design. The population of this this research learners at X finance consisting of 3 classes as much as 106 students. This research uses purposive sampling technique so that the subject of this study are X Finance 1 as experiment class and class X Finance 3 as control class. Methods of data collection using test methods, questionnaires and observations. Data analysis tool used in the form of software IBM SPSS version 25.0. The method of data analysis is non parametric statistical analysis with H1 test using paired sample t-test and H2 test using independent sample t-test. The results showed that there was an increase in learning outcomes after treatment with E-Learning based CMS Wordpress seen from the average pre-test value of 61.60 and post-test value of 77.83, and for student activity increased from 64% to 82 % in the experiment class. It also shows that there is a difference of average result of post experiment class score 77,83 higher than control class post-test equal to 74,04, and for experiment class student activity is 82% higher than control class 81%. Based on the research results, it can be concluded that the use of E-Learning based CMS Wordpress can improve learning outcomes of learners and more effectively improve learning outcomes than using conventional learning. Suggestion given in this research is educator can use E-Learning based CMS Wordpress as one of alternative in learning in class. Keywords: Learning Outcome; Elearning; CMS Wordpress; Students Engagement; Proffesional Ethics